The Role of Islamic Religious Education in Strengthening Religious Moderation in Indonesia - Raito, Raito; Sulaiman, Husnan; Fauziah, Hafsah (LP. Ma'arif Janggan Magetan, 2024)
Religious moderation has become a strategic program of the Indonesian government aimed at strengthening national commitment, tolerance, non-violence, and accommodation of local culture. As a relatively new policy framework, it requires conceptual reinforcement and effective implementation. This study examines the role of Islamic Religious Education in strengthening religious moderation by first analyzing the Qur’anic concept of moderation and identifying key challenges in its application within the Indonesian context. Using a qualitative narrative approach, data were collected through an extensive literature review of books, academic journals, and other credible sources. The findings indicate that IRE plays a crucial role in internalizing moderate religious values by integrating ethical teachings, contextual interpretation of religious texts, and pedagogical practices that encourage dialogue and mutual respect. The analysis further reveals that the effectiveness of IRE in promoting religious moderation depends on a comprehensive educational approach that prioritizes critical thinking, recognition of plurality and pluralism, and appreciation of socio-cultural diversity. This study contributes to scholarly discourse by clarifying the strategic position of IRE in state-led religious moderation efforts and offers policy-relevant insights for strengthening curriculum design and teacher practices to foster a more inclusive and peaceful religious life in Indonesia.